Statics and Mechanics of Materials - Beer, Ferdinand P. (McGraw-Hill Education, 2021)
The approach of the Beer and Johnston series has been appreciated by hundreds of thousands of students over decades of engineering education. Maintaining the proven methodology and pedagogy of the Beer and Johnson series, Statics and Mechanics of Materials combines the theory and application behind these two subjects into one cohesive text focusing on teaching students to analyze problems in a simple and logical manner and, then, to use fundamental and well-understood principles in the solution. The addition of Case Studies based on real-world engineering problems provides students with an immediate application of the theory. A wealth of problems, Beer and Johnston's hallmark sample problems, and valuable review and summary sections at the end of each chapter, highlight the key pedagogy of the text.